Exploring the overshadowed streams of the Red Cross Movement Endeavour and Motivation within and beyond Japan (1867-1919) - Miyagawa, Mayuka Tamura (eCahiers de l'Institut, 2023)
This ePaper explores the endeavours and motivations of the leading figures of the Japanese Red Cross Society, which forms the streams of the Red Cross Movement that get overshadowed in the Eurocentric narrative of its history. Using various primary sources from archives and studying the historical context of the time, the paper highlights how the main protagonists with similar backgrounds to the founders of the International Committee of the Red Cross proactively sought to establish and develop the movement both at the national and international level from 1867 to 1919. Moreover, a close examination of their backgrounds as well as their thoughts as expressed in their writings suggests that their motivations to engage in Red Cross work were multiple and in part, if not entirely, shaped by various needs to fulfil their own desire and sense of obligation. We extend our heartfelt thanks to the Vahabzadeh Foundation for financially supporting the publication of best works by young researchers of the Graduate Institute, giving a priority to those who have been awarded academic prizes for their master's dissertations.